NBW Is Subject of Inquiry by Securities Regulators: FINAL Edition - Brenner, Joel Glenn (The Washington post, 1990)
According to the sources, the SEC is investigating whether NBW improperly invested customer funds in uninsured notes issued by the bank's parent, Washington Bancorporation (WBC), in the weeks before WBC defaulted on those notes. The SEC also is investigating whether WBC failed to disclose to its stockholders that NBW had made loans involving higher than normal risk to a company associated with bank directors, according to documents obtained by The Washington Post. The SEC began its investigation of NBW about a week prior to NBW's annual meeting this spring, sources said, when the commission received a tip that the bank had revised its proxy statement to delete sections indicating that $4.3 million in loans to American Equity were troubled.